Revealing the complete mitogenome sequence of Hypsugo alaschanicus based on next generation sequencing. Issue 2 (12th December 2017) - Shi, Yanshuang; Zhao, Shuai; Han, Xiaomin; Xu, Chunzhu
Abstract: Hypsugo alaschanicus belong to Chiroptera, which is the only type of mammals with the real ability to fly. The complete mitochondrial genome of H. alaschanicus based on next generation sequencing data thus determined had 37 genes for 13 proteins, 22 tRNAs, and 2 rRNAs together with a major non-coding region in a typical gene arrangement of vertebrate mitogenomes. Phylogenetic analysis shows that Pipistrellini is multiline origin, Pipistrellus -like bats can be divided into three groups: Pipistrellini-Nyctalini, Vespertilionini-Eptesicini, and Asian Pipistrelles. Hypsugo alone become a clade, Vespertilio and Eptesicus phylogenetic relationship are closer, Pipistrellus and Nyctalus have a close phylogenetic relationship.